Hierarki Kebutuhan Tokoh Nathan Novel Dear Nathan karya Erisca Febriani Kajian Psikologi Humanistik Abraham Maslow - Nur Erlita Heparinda; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Literary work is a work of imagination expressed in written form by a writer. These literary works are created by writers for aesthetic purposes. Literary works often tell a story, plot, characterization and conflict background. Stories based on essays or true stories produced as literary works, to convey ideas and positive messages from the author to readers. The method used in this research is qualitative analysis and is linked to Maslow's Needs theory. Needs are very often called basic needs which are described as a hierarchy that describes the levels of needs, namely, physiological needs, safety, social needs, ego, and self-actualization. The method used is related to the conditions and situations of the subject in the novel. In the novel Dear Nathan, there are characters that will be discussed, namely Nathan, Salma, Daniel, Ardi (Papa Nathan), and Mama Meli (Mama Nathan), the characters consist of character, protagonist, antagonist, tritagonist. Mixed storyline, sad, happy, touched, regretful. Messages in the novel: Be grateful, learn to understand, give love, be sincere, be loyal, keep promises, make sacrifices, be faithful. In this research, it is hoped that readers can understand the message given by the author.